Internal Conflict of Main Character in the Novel “It Ends with Us” by Collen Hoover - Hamida, Azzahra Muthia; Pertala, Erik Candra; Hestiana, Siska (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research discusses internal conflicts of the main characters in Colleen Hoover's Novel It Ends With Us. The focus of this research is how to depict inner conflict in Colleen Hoover's novel It Ends With Us. The research method used in this research is descriptive qualitative with a goal approach. The results of this study found an analysis of the main character's inner conflict of the main character, Lily expresses all her frustration through the journal she made when she was 15 years old. He tells in detail what happened 10 years ago, which makes him sad and recalls what happened in the past. Keywords: Lily, It Ends with Us, Novel, Conflict, Inner conflict